The Karavas Water Project: an archaeological and environmental study of interaction and community in northern Kythera - Tzortzopoulou-Gregory, Lita (Journal of Greek Archaeology, 2017)
This paper is an attempt to explore how small agricultural communities are able to engage in collective decision-making and constructive collaboration among individuals in the use and management of their limited natural resources, and in particular water, for their own individual benefit and for the benefit of the community at large. The sophisticated use and management of the water system of the small village of Karavas in northern Kythera is a testimony to such community fellowship and solidarity that has survived from at least the beginning of the Early Modern Period (18th century) – if not earlier – until the Present. As the modern settlement developed and expanded around the natural springs and the flowing stream, so did the interconnections among the family-owned vegetable gardens (perivolia) and the numerous water-mills. These mills, in turn, harnessed the power of the flowing water for small-scale ‘industrial’ flour production, serving the local communities and frequently individuals from other settlements farther afield.